Strategi Optimalisasi Dana Desa untuk Mencegah dan Menanggulangi Stunting di Desa Sindangsari, Kabupaten Serang - Fajar Tri Kesuma; Julia Ivanna (Departement of Mathematics Education, 2024)
Overcoming the problem of stunting is a big challenge that requires cross-sector collaboration and increasing public awareness. Stunting is influenced by various factors, with children aged 36-47 months having the highest risk. Lack of maternal knowledge regarding nutrition and quality antenatal and postnatal services are risk factors for stunting. Sindangsari Village, Serang Regency, has allocated village funds for nutrition and health programs, especially through the Healthy Kitchen program. This program not only provides nutritious food, but also empowers people to understand the importance of balanced nutrition. However, challenges such as delays in disbursement of funds and community resistance to the stunting label still need to be overcome. Through a holistic and participatory approach, it is hoped that these programs can be effective in preventing and overcoming stunting at the local level. This research aims to explore strategies for optimizing Village funds in preventing and overcoming stunting in Sindangsari Village, Serang Regency. Qualitative methods are used with a descriptive focus, observing real social conditions using data collection techniques through observation, interviews and documentation. Data analysis was carried out through data reduction, data presentation, and drawing conclusions. It is hoped that the research results will provide an in-depth understanding of how best to utilize Village funds to overcome stunting, especially in the local context of Sindangsari Village.